Cell Membrane Coated-Biomimetic Nanoplatforms Toward Cancer Theranostics - Li, Tingting; Qin, Xiang; Li, Yichao; Shen, Xue; Li, Shun; Yang, Hong; Wu, Chunhui; Zheng, Chuan; Zhu, Jie; You, Fengming; Liu, Yiyao (Frontiers in Bioengineering and Biotechnology, 2020)
Research of nanotechnology for cancer therapy and diagnosis extends beyond drug delivery into the targeted site or surveillance the distribution of nanodrugs in vivo or distinction tumor tissue from normal tissue. To satisfy the clinic needs, nanotheranostic platform should hide the surveillance by immune system and the sequestration by filtration organs (i.e., liver and spleen). Use of biologically derived cellular components in the fabrication of nanoparticles can hide these barriers. In this review, we update the recent progress on cell membrane-coated nanoparticles for cancer theranostics. We hope this review paper can inspire further innovations in biomimetic nanomedicine.